2009
DOI: 10.2478/s11534-009-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Interface resistive switching effects in bulk manganites

Abstract: Abstract:A physical mechanism driving the resistance switching in heterocontacts, formed by a metal counterelectrode and electrically conducting bulk perovskite manganites, is discussed. The nature of the inelastic, charge-hopping transport inside insulating and strongly inhomogeneous metal/manganite interfaces is studied theoretically. Comparison with measured current-voltage characteristics for a La 0 67 Ca 0 33 MnO 3 /Ag heterostructure in a high-resistance state reveals the presence of one or more charge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
9
0
4
Order By: Relevance
“…3 Many binary oxides and perovskite transition metal oxides, e.g. titanates, 4, 5 zirconates, 6,7 and manganites, 8,9 have been investigated as the switching element. 10 Over the years, different models have been proposed to explain the resistive switching phenomona.…”
mentioning
confidence: 99%
“…3 Many binary oxides and perovskite transition metal oxides, e.g. titanates, 4, 5 zirconates, 6,7 and manganites, 8,9 have been investigated as the switching element. 10 Over the years, different models have been proposed to explain the resistive switching phenomona.…”
mentioning
confidence: 99%
“…Further investigations [6] have confirmed the presence of the effect in a high-T c superconductor BiSrCaCuO and showed that it is observed up to room temperature. Experiments performed on four-component Mnbased compounds revealed the presence of resistive switchings in this class of materials as well [7,8].…”
Section: Resistive Switching Phenomenon In Transition-metal Oxidesmentioning
confidence: 99%
“…Δε ≤ ε − ε -энергия испускаемого бозона) совпадают [40,41]. Далее предположим, что внутри дефектного диэлектрического слоя, размеры которого в поперечных нормали направлениях являются макроскопическими, имеется множество локализованных состояний, и поэтому электронное туннелирование сквозь него может осуществ-ляться самыми различными способами, из которых для нас важней-шими являются те, которые приводят к максимуму туннельной прово-димости.…”
unclassified
“…В следующем подразделе приведены экспериментальные данные, под-тверждающие степенную зависимость σ inel (V) в достаточно широкой области напряжений с показателем степени, близким к 1,33, не-смотря на то, что фононные энергии ω в исследованных диэлектри-ческих слоях были достаточно большими и, вряд ли, могли быть адекватно описаны дебаевским приближением ω = v s q. Согласно ра-боте [41] совпадение экспериментальных и теоретических зависимо-стей в этих случаях является случайным и связано с тем, что соот-ветствующие функции электрон-фононного взаимодействия α T ε ε ∝ ε − ε , что в точности соответ-ствует результату Глазмана-Матвеева (17). Подчеркнем, что ре-зультаты двух принципиально различных приближений α 2 F(ω) сов-падают только для описанной выше двухдефектной конфигурации [41]. Некоторые выводы, которые получаются в рамках аппрокси-мации α 2 F(ω) ≈ const, будут приведены в следующем подразделе.…”
unclassified
See 1 more Smart Citation